Human endogenous retroviruses sequences expression in patients with progressive systemic sclerosis and different clinical forms of psoriasis - Namysł, Jakub; Osmola, Agnieszka; Prokop, Janusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
The probable involvement of human endogenous retroviruses (HERV) in the development of autoimmune diseases, especially in systemic lupus erythematosus (SLE) has been long discussed. In a number of reports some indirect evidences implicating retroviruses in human autoimmune diseases have been shown. The aim of this paper was to analyse the level of chosen HERVs in the light of present knowledge about pathological mechanisms typical especially for progressive systemic sclerosis (PSS) and different clinical forms of psoriasis.